2012
DOI: 10.1097/sla.0b013e31823899f8
|View full text |Cite
|
Sign up to set email alerts
|

Reflux and Belching After 270 Degree Versus 360 Degree Laparoscopic Posterior Fundoplication

Abstract: Two hundred seventy degrees LPF and 360 degrees LPF alter the belching pattern by reducing GBs (air venting from stomach) and increasing SGBs (no air venting from stomach). However, gas reflux and GBs are reduced less after 270 degrees LPF than after 360 degrees LPF, resulting in more air venting from the stomach and less gas bloating and flatulence, whereas reflux is reduced to a similar extent in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 51 publications
7
24
2
Order By: Relevance
“…Our study demonstrates that the total number of acid and weakly acidic reflux episodes at 14 years (15.0) are similar to results previously reported 16 at 6 months after Nissen fundoplication (7.4). In contrast, the total number of reflux episodes at 14 years is higher after anterior 180˚ fundoplication (40.4), with more liquid and mixed reflux episodes than after Nissen fundoplication.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study demonstrates that the total number of acid and weakly acidic reflux episodes at 14 years (15.0) are similar to results previously reported 16 at 6 months after Nissen fundoplication (7.4). In contrast, the total number of reflux episodes at 14 years is higher after anterior 180˚ fundoplication (40.4), with more liquid and mixed reflux episodes than after Nissen fundoplication.…”
Section: Discussionsupporting
confidence: 91%
“…19 It has recently been demonstrated that gas reflux and gastric belches are reduced less after posterior 270˚ partial fundoplication, resulting in fewer gas-related symptoms than after Nissen fundoplication at 6 months. 16 The long-term results evaluated in our current study were different. The number of gas reflux episodes at 14 years after anterior 180˚ (37.8) and Nissen fundoplication (55.8) were similar to the preoperative numbers described 16 for anterior 180˚ and Nissen fundoplication (36.3).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations